Level of Nomophobia among Smartphone-Using Teenager at Senior High School 8 Pontianak - Adinda, Nurul Aulia; Putri, Triyana Harlia; Rahmawati, Nadia (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2025)
Teenagers in the era of the industrial revolution 4.0 have become adept at using advanced technology devices, such as smartphones. The massive and continuous use of smartphones can lead to negative impacts, one of which is nomophobia. Nomophobia (no-mobile-phone phobia) is a syndrome experienced by individuals due to being distant from or lacking access to a smartphone. This study aimed to identify the level of nomophobia among teenager smartphone users at Senior High School 8 Pontianak. This research was a quantitative descriptive study with the sample consisting of 240 respondents from grade XI and XII students at Senior High School 8 Pontianak, selected using a purposive sampling technique. Data collection was conducted using the Nomophobia Questionnaire (NMP-Q) instrument and analyzed using univariate analysis with computer software. The univariate analysis showed that 33 respondents (13.83%) experienced low levels of nomophobia, 165 respondents (68.8%) experienced moderate levels of nomophobia, and 42 respondents (17.5%) experienced high levels of nomophobia. The level of nomophobia among teenage smartphone users at Senior High School 8 Pontianak was predominantly in the moderate category.